2022
DOI: 10.1094/phyto-11-21-0457-r
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Analysis Reveals that the Antimicrobial Kasugamycin Potential Targets Nitrate Reductase inDidymella segeticolato Achieve Control of Tea Leaf Spot

Abstract: Due to the lack of effective disease management measures, tea leaf spot, caused by the fungal phytopathogen Didymella segeticola (Q. Chen) Q. Chen, Crous & L. Cai (syn. Phoma segeticola), is an important foliar disease. The important and widely used agricultural antimicrobial kasugamycin (Ksg), produced by the Gram-positive bacterium Streptomyces kasugaensis, effects high levels of control against crop diseases. The results of the current study indicated that Ksg could inhibit the growth of D. segeticola h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Reactive oxygen species (ROS) played important roles in plant immunity (Qi et al, 2017), while SsNR-silenced mutants showed more sensitivity to H 2 O 2 compared to WT resulting in decreased virulence in plants (soybean and rapeseed). Similar results were obtained in the tea leaf spot which is caused by Didymella segeticola, the antimicrobial kasugamycin inhibits the pathogen by binding to NR, disturbing fungal metabolism with changes in hyphal growth and development (Jiang et al, 2022).…”
Section: Discussionsupporting
confidence: 75%
“…Reactive oxygen species (ROS) played important roles in plant immunity (Qi et al, 2017), while SsNR-silenced mutants showed more sensitivity to H 2 O 2 compared to WT resulting in decreased virulence in plants (soybean and rapeseed). Similar results were obtained in the tea leaf spot which is caused by Didymella segeticola, the antimicrobial kasugamycin inhibits the pathogen by binding to NR, disturbing fungal metabolism with changes in hyphal growth and development (Jiang et al, 2022).…”
Section: Discussionsupporting
confidence: 75%
“…Kasugamycin (KAS) is an agricultural antibiotic produced by streptomycetes that can effectively kill bacteria by interfering with protein synthesis. This antibiotic is widely used for the treatment of many agricultural diseases, 34,35 owing to high efficiency, low toxicity and broad antibacterial spectrum. Structurally speaking, KAS belongs to aminoglycosides, having both an acidic group and basic groups.…”
Section: Introductionmentioning
confidence: 99%
“…As an aminoglycoside antibiotic isolated from Streptomyces kasugaensis , kasugamycin (KSM) has excellent antimicrobial activity against Erwinia amylovora , Aciovorax citrulli , Didymella segeticola , Rhizoctonia solani , Cercospora janseana , and Magnaporthe oryzae [ 23 , 24 , 25 , 26 , 27 ]. Application of KSM before disease occurrence is an effective method to avoid the outbreak of plant diseases in the field.…”
Section: Introductionmentioning
confidence: 99%